2015
DOI: 10.1016/j.redox.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Border between natural product and drug: Comparison of the related benzoquinones idebenone and coenzyme Q10

Abstract: Coenzyme Q10 is a ubiquitous component of cellular membranes and belongs to the class of benzoquinones that mainly differ with regards to the length and composition of their hydrophobic tail. The characteristic quinone group can accept electrons from various biological sources and is converted by a one electron transfer to the unstable semiquinone or by a two electron transfer to the more stable hydroquinone. This feature makes CoQ10 the bona fide cellular electron transfer molecule within the mitochondrial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 43 publications
0
63
0
1
Order By: Relevance
“…Coenzyme Q10 is rather lipophilic and has poor pharmacokinetic properties, which is the reason why idebenone is preferred in therapeutic studies. 24 We directly examined the effects of idebenone on TMEM16A in patch clamp recordings. tBHP activated large Cl 2 -selective whole-cell currents in TMEM16A-expressing HEK293 cells but not in mock transfected cells ( Figure 6, A and B).…”
Section: Oxidative Stress Induces Growth and Expansion Of Mdck Cystsmentioning
confidence: 99%
“…Coenzyme Q10 is rather lipophilic and has poor pharmacokinetic properties, which is the reason why idebenone is preferred in therapeutic studies. 24 We directly examined the effects of idebenone on TMEM16A in patch clamp recordings. tBHP activated large Cl 2 -selective whole-cell currents in TMEM16A-expressing HEK293 cells but not in mock transfected cells ( Figure 6, A and B).…”
Section: Oxidative Stress Induces Growth and Expansion Of Mdck Cystsmentioning
confidence: 99%
“…Due to the indispensable function in the processes of oxidative phosphorylation, Coenzyme Q-10 (CoQ-10) and its derivatives are the most prominent members in the family of Q/HQ [4][5][6][7]. Although the number of studies related to the chemical and redox features of CoQ family members has increased tremendously in the last three decades [8][9][10][11][12][13][14][15][16][17][18], many key features are still not well understood. In our last two publications we have shown that Coenzyme Q-1 (CoQ-1) and CoQ-10 undergo structural changes in strong alkaline environment or in the presence of Cytochrome P450 enzymes [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Idebenone is a synthetic short-chain benzoquinone that, like coenzyme Q10, carries energy equivalents within the electron transport chain. Unlike coenzyme Q10, however, idebenone also shuttles energy equivalents from the cytosol to the electron transport chain [40]. Thus, the facilitation of metabolic pathways is the rationale for its potential effect in DMD.…”
Section: Other Mechanismsmentioning
confidence: 99%